A mini review of conflict management styles in workplaces: the significance of community psychology approach - Mehrad, Aida; Hamsan, Hanina Halimatusaadiah; Redzuan, Ma'rof (American-Eurasian Network for Scientific Information, 2014)
Conflict management is as a main method in every organization which restricting the negative facets of conflict at workplace and lead to appear positive signs of conflict in organization. This industrial and organizational phenomenon raises knowing and applying correct styles of management for conducting managers in organization. In reality, conflict is an abnormal social phenomenon which has various effects on organizations’ outcome. In this way, monitoring these various effects can open new view in organizational process. The Presence of correct conflict management improve amount of mental health and psycho among managers in organization and reduce abnormal reactions against another staffs. Community psychology can do this fact with determined some efficiency policies in society. Therefore conflict management has an important and noticeable key role in organization ‘achievement and outcomes. Furthermore, the ability to contact with conflict and solving it has valuable duty for managers’ successfully and organization. In this case, Community psychology provide sufficient platform for conflict styles and determine some intervention and prevention for them. These strategic items (intervention and prevention) cover managers’ benefits and organization correctly with attention to conflict styles. Conflict management involves five styles which by them manage and limit abnormalities behaviors in correct way at work place :1) Collaboration pays attention to both side of discussion and develop their desire by cooperating and listening together, 2) Compromising tries to find a suitable solution and determine duties between both side (manager and staff), 3) Accommodation refers to other points and usually follow their suggestion 4) Competing mentions the rights and believes of managers and staffs in accurate way and finally 5) Avoiding refers to both side which do not cooperate together and never try to solving their problem. In this style, just one side of conflict try to find solution way and avoid to appear another difficulty.